HUBUNGAN ANTARA KOMPETENSI PROFESIONAL DAN MOTIVASI BERPRESTASI DENGAN KREATIVITAS KERJA GURU - Sugiarti Sugiarti; Rita Retnowati; Eka Suhardi (JURNAL MANAJEMEN PENDIDIKAN, 2018)
The teachers creativity is a behavior that shows acceptance and implementation of performance changes either in the form of ideas, processes or products that have added values to achieve the goals of quality education. This study is a correlation research consisting of two independent variables and one dependent variable, namely the teachers professional commpetence and achievement motivation with teachers working creativity. This research was carried out in 20 of State Elementary School in North Telukjambe Region of Karawang district in west java with total population are 198 state teacher, using survey method. The total sample are 133. The sampling technique is the proportional random sampling. The data were analyzed using correlational and simple linier regressional statistical technique. The hypothesis were tested at the 0.05 significance level. The research result shows that 1) there is positive correlation between a teachers professional commpetence (X1) with teachers creativity (Y) with an rx1y = 0.417 with regression equation ? = 133.5 + 1.186 X1, 2) there is positive correlation between teachers creativity (X2) with teachers working creativity with an rx2y = 0.456 with regression equation ? = 51.91+ 0.753X2, 3) there is positive correlation between a teachers professional commpetence and achievement motivation together with teachers creativity with an rx1x2y = 0.554 with regression equation ? = 49.420 + 0.919X1 + 0.620X2. The implications of this research is to increase of the creativity of teacher that can be done by increasing indicators of teachers professional commpetence and achievement motivation variables, either individually or collectively.Keyword: Teachers Creativity, Professional Commpetence, Achievement Motivation